The malS-5′UTR weakens the ability of Salmonella enterica serovar Typhi to survive in macrophages by increasing intracellular ATP levels. (February 2018) - Dong, Fang; Xia, Lin; Lu, Renfei; Zhao, Xin; Zhang, Yiquan; Zhang, Ying; Huang, Xinxiang
Abstract: Bacterial non-coding RNAs (ncRNAs), as important regulatory factors, are involved in many cellular processes, including virulence and protection against environmental stress. The 5′ untranslated region (UTR) of malS (named malS -5′UTR), a regulatory ncRNA, increases the invasive capacity and influences histidine biosynthesis in Salmonella enterica serovar Typhi ( S. Typhi). In this study, we found that overexpression of the malS -5′UTR decreased S. Typhi survival within macrophages. A microarray analysis of a strain overexpressing the malS -5′UTR revealed a significant increase in the mRNA levels of the atp operon. The intracellular ATP levels were elevated in the malS -5′UTR overexpression strain. Quantitative real-time polymerase chain reaction results showed that the malS -5′UTR downregulated the mRNA levels of phoP, phoQ, and mgtC. MgtC, its expression is regulated by PhoP/PhoQ two-component regulatory system, inhibits the F1F0 ATP synthase, thereby preventing the accumulation of ATP to non-physiological levels and the acidification of the cytoplasm within macrophages. Thus, we propose that the malS -5′UTR weakens the ability of S . Typhi to survive in macrophages, probably because of the accumulation of ATP within macrophages, by regulating the mRNA levels of mgtC and the atp operon in a phoP -dependent manner. Highlights: The malS -5′UTR may function as an ncRNA to weaken the ability of S. Typhi to survive in macrophages. The malS -5′UTR increases the atp operon level in S. Typhi by downregulating the mgtC mRNA level in a phoP -dependent manner. The malS -5′UTR increases intracellular ATP levels, which leads to lower intracellular survival of S. Typhi in macrophage.